Analysis of a phase change material-based unit and of an aluminum foam/phase change material composite-based unit for cold thermal energy storage by numerical simulation. (15th December 2019) - Caliano, Martina; Bianco, Nicola; Graditi, Giorgio; Mongibello, Luigi
Highlights: Two different PCM-based cold thermal energy storage units are numerically analysed. One unit includes a bio-PCM, while the other one also includes an aluminum foam. With only PCM, free convection is crucial during cooling energy discharging. The cooling energy charging process is more sensible to the presence of the foam. Free convection within the PCM is negligible in the case with the foam. Abstract: Thermal energy storage systems have increasingly attracted researchers and engineers in the last decades, not only because they permit to overcome the mismatch between thermal energy supply and demand in solar thermal systems, but also because they have the potential to improve the power grid reliability and flexibility, as they allow, for example, to store the heat or the cooling energy produced by residential electric heat pumps for a later use. In this context, this work analyses the cooling energy charging and discharging of two different cold thermal energy storage units, based on the use of a phase change material (PCM), by numerical simulation. One unit consists of an aluminum cylindrical container partially filled with a biological PCM. The other one is similar, with the only difference that it also includes an aluminum metal foam immersed in the PCM. Two different 2D axisymmetric models have been developed, both based on the effective heat capacity method in order to account for the PCM latent heat, for the numerical simulation of the two different units, and the numerical results are compared with experimental ones, obtained by means of a climatic chamber, in order to assess, in each case, the best set of the model arbitrary parameters among the considered ones. Moreover, for each simulation model, a sensitivity analysis is performed to show the effects of two arbitrary model parameters on the numerical results. Simulation results relative to the unit with only the PCM indicate that the cooling energy charging is most affected by conductive heat transfer, and in particular by the thermally resistive layer of solid PCM that forms at the lateral wall of the aluminum container, and that heat transfer by free convection plays a crucial role in the cooling energy discharging process. As concerns the unit with the PCM and the aluminum foam, numerical results show that the charging process and the discharging one are about four times and two times faster than without the foam, respectively. Furthermore, numerical results show that, with the employed aluminum foam, free convection within the PCM is negligible in both the cooling energy charging and discharging process.